The Effectiveness of Patience Therapy with Sufistic Techniques in Increasing Resilience in Adolescents - Dhika Fitri Herliana; Aditi Pant (Pamomong: Journal of Islamic Educational Counseling, 2023)
This study aimed to: 1) determine the condition of adolescents' resilience before receiving patience therapy 2) determine the condition of adolescents' resilience after receiving patience therapy 3) determine the effectiveness of guidance service with patience therapy in increasing adolescents' resilience. This quantitative study applied one group pre-test and post-test. Data were collected through questioinnaire, which was distributed to twenty participants. The study results indicate that before receiving patience therapy with sufistic techniques, adolescents exhibited a mean score of 164.5 or 82%, which was grouped into moderate category. After receiving patience therapy with sufistic techniques, the mean score was 171.35 or 86%, which was in the high category. This is proven through the Paired t-test sample test, which obtained a sig. (2-tailed) of 0.000 0.05, indicating that patience therapy with Sufistic techniques is effective in improving adolescents' resilience